Shrimp sauce from enzyme-treated shrimp waste powder - Dela Cruz, Miren S.
The possibility of utilizing shrimp waste, as shrimp waste powder, in making shrimp sauce was explored. The shrimp waste powder was treated with the enzyme Neutrase to increase its protein content. The enzyme-treated powder gave a value of 6.81% protein content. Prior to treatment of the enzyme, the shrimp waste powder contained 3.8% protein. Based on results of the sensory evaluation, the enzyme-treated shrimp powder was preferred than the shrimp powder without enzyme treatment. The enzyme-treated powder was characterized as pinkish brown in color, a fine texture, a slight shrimp odor, and a hedonic rating of like moderately. The powder without enzyme treatment was described as light brown in color, a grainy texture, a characteristic shrimp odor, and a hedonic rating of like slightly. The most acceptable formulation for the production of shrimp sauce contained 20 grams of shrimp waste powder, 30 grams all-purpose flour, one cup of cooking oil with extracted annatto dye (one tablespoon), one tablespoon pounded garlic, one cup sliced onion, one-half teaspoon salt, and one-half teaspoon MSG. The formulation yielded 230 grams of shrimp sauce sufficient for one recipe of pancit palabok. The shrimp sauce was characterized as reddish orange in color, slight shrimp odor, a smooth texture, with a characteristic shrimp flavor, and a hedonic rating of like moderately.